Influence of NH3 CO2 activation on the CO2 H2S adsorption capacity of cellulose char - Navarro Gil, África; Gil-Lalaguna, Noemí; Fonts, Isabel; Ruiz, Joaquín; ceamanos, Jesús; Ábrego, Javier; Gea, Gloria (Jornada de Jóvenes Investigadores del I3A, 2023)
Anaerobic co-digestion is an attractive opportunity for the energetic valorization of several organic residues generated in the livestock and agricultural sector. A combustible biogas is obtained, that could be used as a source of energy on the farm. The biogas is mainly composed of CH4, CO2 and trace amounts of other components such as H2S. However, to reduce gas emissions  and broaden the application of biogas as a fuel or as bio-methane, the concentration of CO2 and H2S must be decreased. This study examines the effect of NH3 functionalization and/or CO2 activation (at 700 ºC) of cellulose pyrolysis chars (produced at 750 ºC) on the adsorption of CO2 and H2S from a gas stream.